Brain Drain in Finland; A Real Threat or a Myth and its Impact on Finland's R&D Capabilities - Zaraf, Afnan; Kantola, Jussi (Politechnika Śląska, 2019)
The phenomenon of ‘Brain Drain’ or ‘Human Capital Flight’ is actively discussed in Finland recently. It is the phenomenon in which highly educated and skilled people leave the country where they attained their education and skills. The official statistics and data show that it is an alarming situation with every passing year in Finland. The phenomenon is widely observed in all sectors, but the most affected sectors are research-based fields, natural sciences, biosciences, humanities, anthropology, psychology, statistics, and core-engineering fields. However, is this really a brain drain phenomenon or something else? The focus of this paper is to explore the brain drain phenomenon’s existence in Finland based on officially available data. The paper also investigates the main causes of brain drain, its future effects on Finland’s R&D capabilities and the Finnish economy. This is a review article about the brain drain phenomenon based on previous studies and official quantitative data from Statistics Finland. This paper serves as the basis for the development of a research instrument to further analyze the situation in future research. ; Zjawisko „drenażu mózgów” (ang. brain drain lub human capital flight) stało się ostatnio przedmiotem intensywnie dyskutowanym w Finlandii. Jest to zjawisko, gdy wysoko wykształceni i wykwalifikowani ludzie opuszczają kraj, w którym zdobyli wykształcenie i umiejętności. Oficjalne statystyki i dane pokazują, że w tym zakresie sytuacja w Finlandii staje się coraz bardziej alarmująca z każdym rokiem. Zjawisko to jest powszechnie obserwowane we wszystkich sektorach, ale najbardziej nim dotknięte są sektory, których działanie opiera się na badaniach, nauki przyrodnicze, biologiczne, humanistyczne, antropologiczne, psychologiczne, statystyczne oraz techniczne. Jednak czy to naprawdę zjawisko drenażu mózgów czy coś innego? Celem artykułu jest zbadanie istnienia zjawiska drenażu mózgów w Finlandii na podstawie oficjalnie dostępnych danych. W artykule przeanalizowano również główne przyczyny drenażu mózgów oraz jego skutki dla fińskiego potencjału badawczo-rozwojowego i fińskiej gospodarki. Jest to artykuł przeglądowy, dotyczący zjawiska drenażu mózgów na podstawie wcześniejszych badań i oficjalnych danych ilościowych z fińskiego urzędu statystycznego (Statistics Finland). Niniejszy artykuł posłuży jako podstawa do opracowania instrumentu badawczego i przyszłych badań w celu przeanalizowania rzeczywistej sytuacji w przyszłości.
Keywords: human capital flight; R&D; Finland; brain drain; innovations; fi=Tuotantotalous|en=Industrial Management|